POSTMENOPAUSAL MOTHERHOOD: IMMORAL, ILLEGAL? A CASE STUDY - Cutas, Daniela (Bioethics, 2007)
The paper explores the ethics of post-menopausal motherhood by looking at the case of Adriana Iliescu, the oldest woman ever to have given birth (so far 1). To this end, I will approach the three most common objections brought against the mother and/or against the team of healthcare professionals who made it happen: the age of the mother, the fact that she is single, the appropriateness of her motivation and of that of the medical team.